نماذج من رحلات العلم لشيوخ جبل نفوسة (الدوافع والأهمية) حتى (القرن الثامن الهجري / الرابع عشر الميلادي). - د. علي حامد الطيف (Sharwes Scientific Journal, 2025)
) The topic of Examples of the Scholarly Journeys of the Sheikhs of Mount Nafusa (Motives and Importance) until the Eighth Century AH / Fourteenth Century AD summarizes a selected study of a number of the scholarly journeys of the Sheikhs of Mount Nafusa in terms of motives, importance, and temporal diversity, and their effects on the development of intellectual life. The sheikhs of knowledge had Nafusa Mountain played a major role in exporting scientific endeavors, after they were able to achieve primacy in the field of science, which allowed them to organize several trips to various countries, east and west.